The relationship between social cognition and executive function in Major Depressive Disorder in high-functioning adolescents and young adults. (May 2018) - Förster, Katharina; Jörgens, Silke; Air, Tracy M.; Bürger, Christian; Enneking, Verena; Redlich, Ronny; Zaremba, Dario; Grotegerd, Dominik; Dohm, Katharina; Meinert, Susanne; Leehr, Elisabeth J.; Böhnlein, Joscha; et al.
Abstract: To understand how cognitive dysfunction contributes to social cognitive deficits in depression, we investigated the relationship between executive function and social cognitive performance in adolescents and young adults during current and remitted depression, compared to healthy controls. Social cognition and executive function were measured in 179 students (61 healthy controls and 118 patients with depression; M age = 20.60 years; SD age = 3.82 years). Hierarchical regression models were employed within each group (healthy controls, remitted depression, current depression) to examine the nature of associations between cognitive measures. Social cognitive and executive function did not significantly differ overall between depressed patients and healthy controls. There was no association between executive function and social cognitive function in healthy controls or in remitted patients. However, in patients with a current state of depression, lower cognitive flexibility was associated with lower performance in facial-affect recognition, theory-of-mind tasks and overall affect recognition. In this group, better planning abilities were associated with decreased performance in facial affect recognition and overall social cognitive performance. While we infer that less cognitive flexibility might lead to a more rigid interpretation of ambiguous social stimuli, we interpret the counterintuitive negative correlation of planning ability and social cognition as a compensatory mechanism. Highlights: Executive function is associated with social cognition only during current depression. Enhanced planning ability might compensate for social cognitive dysfunction. Reduced cognitive flexibility might lead to a rigid interpretation of social stimuli. The results cannot be attributed to age or chronicity of depression. The method investigates prosody, facial affect recognition and theory of mind.